Self-Confidence and Reactions to Subjective Performance Evaluations - Charles Bellemare; Alexander Sebald (Institute of Labor Economics (IZA), 2019)
Subjective performance evaluations are commonly used to provide feedback and incentives to workers. However, such evaluations can generate significant disagreements and conflicts, the severity of which may be driven by many factors. In this paper we show that a workers' level of self-confidence plays a central role in shaping reactions to subjective evaluations - overconfident agents engage in costly punishment when they receive evaluations below their own, but provide limited rewards to principals when evaluations exceed their own. In contrast, underconfident agents do not significantly react to evaluations below their own, but reward significantly evaluations exceeding their own. Our analysis exploits data from a principal-agent experiment run with a large sample of the Danish working age population, varying the financial consequences associated with the evaluations workers receive. In contrast to existing economic models of reciprocal behavior, reactions to evaluations are weakly related to the financial consequences of the evaluations. These results point towards a behavioral model of reciprocity that intertwines the desire to protect self-perceptions with over-/underconfidence.
Keywords: D01; D02; D82; D86; J41; 330; subjective performance evaluations; self-confidence; reciprocity